Profiling of MicroRNAs Involved in Mepiquat Chloride-Mediated Inhibition of Internode Elongation in Cotton (Gossypium hirsutum L.) Seedlings - Wang, Li; Yin, Ying; Jing, Xiuxiu; Wang, Menglei; Zhao, Miao; Yu, Juanjuan; Qiu, Zongbo; Li, Yong-Fang (Frontiers in Plant Science, 2021)
Mepiquat chloride (MC) is the most important plant growth retardant that is widely used in cotton (Gossypium hirsutum L.) production to suppress excessive vegetative growth and improve plant architecture. MicroRNAs (miRNAs) are important gene expression regulators that control plant growth and development. However, miRNA-mediated post-transcriptional regulation in MC-induced growth inhibition remains unclear. In this study, the dynamic expression profiles of miRNAs responsive to MC in cotton internodes were investigated. A total of 508 known miRNAs belonging to 197 families and five novel miRNAs were identified. Among them, 104 miRNAs were differentially expressed at 48, 72, or 96 h post MC treatment compared with the control (0 h); majority of them were highly conserved miRNAs. The number of differentially expressed miRNAs increased with time after treatment. The expression of 14 known miRNAs was continuously suppressed, whereas 12 known miRNAs and one novel miRNA were continuously induced by MC. The expression patterns of the nine differentially expressed miRNAs were verified using qRT-PCR. The targets of the known and novel miRNAs were predicted. Four conserved and six novel targets were validated using the RLM-5′ RACE assay. This study revealed that miRNAs play crucial regulatory roles in the MC-induced inhibition of internode elongation. It can improve our understanding of post-transcriptional gene regulation in MC-mediated growth inhibition and could potentially facilitate the breeding of dwarf cotton.